EFFECT OF WEIGHT TRAINING ON LOWER LIMB STRENGTH IN SOCCER PLAYERS - Yi,Yan (2022)
ABSTRACT Introduction: There are many methods for lower limb explosive strength training in soccer athletes, and the most common is strength gain training by load increase. There is still no consensus on whether this type of training can influence jumping performance in soccer athletes. Objective: To explore the influence of muscle gain by added weight on jumping performance and lower limb muscle strength in soccer athletes. Methods: 60 participants were equally divided between high, low, and control training groups. The load was implemented with a weight vest for eight weeks. The training frequency was 40 to 60 minutes three times a week, and the training protocols and schedules of the two groups were the same, while the control group was not involved in any sports training. Results: The isokinetic muscle strength test of the left knee extensor before and after eight weeks of training showed no significant interaction between maximum torque and time to reach maximum torque at 60°/s and 180°/s (P > 0.05). After the jump test, a significant difference appears in the main effects on time factors between group A and group B. Conclusion: Strength training by load addition is an effective training method to improve the sport’s ability in the lower limbs of soccer athletes. Evidence Level II; Therapeutic Studies - Investigating the result.